Collaboration for Sustainable Intensification: The Underpinning Role of Social Sustainability. Issue 1 (16th October 2019) - Wynne‐Jones, Sophie; Hyland, John; Williams, Prysor; Chadwick, Dave
Abstract: Sustainable Intensification (SI) has been popularised in recent years as an approach seeking to balance the potentially conflicting demands of enhancing agricultural outputs with reducing the negative impacts arising from the current food system. Proponents have argued that SI can benefit from collaboration between farmers, but understanding is limited by a lack of data on current collaborative practices. Questions have also been raised as to whether the SI agenda pays sufficient attention to social sustainability as part of a fully integrated conception of SI. Tackling these issues, this paper reports on mixed methods data collection from seven case areas across the UK, with a particular focus on the experience of upland livestock farmers in north Wales. We evidence: (1) The extent, forms and preferences associated with farmers' collaboration; with findings demonstrating higher levels of collaboration than anticipated and a preference for informal forms of co‐working. (2) The underpinning and mutually reinforcing role of social interconnectedness in the delivery of diverse outcomes from collaboration. (3) How SI is perceived to threaten social sustainability, and thus work against a more integrated model of delivery. The paper concludes by arguing for a genuinely integrative model of SI to secure collaborations going forwards.